2006
DOI: 10.1086/500469
|View full text |Cite
|
Sign up to set email alerts
|

Two‐Year Prospective Study of the Humoral Immune Response of Patients with Severe Acute Respiratory Syndrome

Abstract: In a cohort study of 56 convalescent patients with severe acute respiratory syndrome (SARS), titers of immunoglobulin G (IgG) antibodies and neutralizing antibodies (NAbs) against SARS-associated coronavirus were assessed at regular intervals (at 1, 4, 7, 10, 16, and 24 months after the onset of disease) by use of enzyme-linked immunosorbent assay and neutralization assay. IgG antibody and NAb titers were highly correlated, peaking at month 4 after the onset of disease and decreasing thereafter. IgG antibodies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
268
0
15

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 293 publications
(291 citation statements)
references
References 13 publications
8
268
0
15
Order By: Relevance
“…As seen in our previous studies (4,6), the humoral immunity continuously declined over time and eventually vanished in most patients. Only 2 of 23 patients maintained a low level of IgG Ab 6 y after disease onset.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As seen in our previous studies (4,6), the humoral immunity continuously declined over time and eventually vanished in most patients. Only 2 of 23 patients maintained a low level of IgG Ab 6 y after disease onset.…”
Section: Discussionsupporting
confidence: 79%
“…Previous studies indicated that specific Abs to SARS-related coronavirus (SARS-CoV) waned over time. (4)(5)(6)(7)(8)(9) However, disappearance of anti-SARS-CoV Abs does not necessarily indicate loss of protection. As is well known, an efficient line of defense against viral reinfection consists of three key components: preexisting Abs, memory B cells, and memory T cells.…”
Section: S Evere Acute Respiratory Syndrome (Sars) Is An Emerging Infmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum IgG, IgM, and IgA responses to SARS-CoV occurred around the same time, with most patients seroconverting by day 14 after onset of illness (135). In a follow-up study of 56 subjects, ELISA IgG and neutralizing antibodies peaked at 4 months and dropped progressively over time; 11% of the subjects did not have detectable ELISA IgG antibodies to SARS 24 months postinfection, but neutralizing antibodies were still detectable (136). In a large study of 623 SARS patients, antibodies were able to neutralize pseudotyped viruses bearing S proteins from four different SARSCoV strains, suggesting that these antibodies were cross-reactive (137).…”
Section: Humoral Immune Response To Sars-cov Infectionmentioning
confidence: 97%
“…Persistent levels of SARS-CoV IgG have been detected in SARS cases for several months and up to 2 years after disease onset (4,11,12,19,21). In this study, serum samples from 48 SARS patients from Vietnam and the United States were collected 221 to 735 days (44 from days 221 to 250; 4 from days 633 to 735) after the onset of illness and tested for the presence of SARS-CoV-and N-and S-protein-specific IgG by ELISA.…”
mentioning
confidence: 99%